Rhabdomyosarcoma diagnosed in the first year of life: Localized, metastatic, and relapsed disease. Outcome data from five trials and one registry of the Cooperative Weichteilsarkom Studiengruppe (CWS). Issue 6 (14th February 2019) - Sparber‐Sauer, Monika; Stegmaier, Sabine; Vokuhl, Christian; Seitz, Guido; von Kalle, Thekla; Scheer, Monika; Münter, Marc; Bielack, Stefan S.; Weclawek‐Tompol, Jadwiga; Ladenstein, Ruth; Niggli, Felix; Ljungman, Gustaf; et al.
Abstract: Background: Rhabdomyosarcoma (RMS) diagnosed during the first year of life is reported to have poor outcome. Little is known about treatment and outcome data of relapsed disease (RD). Methods: Characteristics, treatment, and outcome of 155 patients ≤ 12 months registered within the Cooperative Weichteilsarkom Studiengruppe (CWS) between 1981 and 2016 were evaluated. Results: Localized disease (LD) was diagnosed in 144 patients and metastatic disease (MD) in 11. The histological diagnosis was alveolar (RMA) ( n = 38, 23/25 examined patients PAX7/3:FOXO1‐positive), embryonal (RME) ( n = 100), botryoid ( n = 10), anaplastic ( n = 1), and spindle‐cell RMS ( n = 6). Multimodal treatment including conventional (age‐adjusted) chemotherapy (CHT) ( n = 150), resection ( n = 137), and radiotherapy (RT) ( n = 37) was administered. Complete remission was achieved in 129 of 144 patients with LD. RD occurred in 51 infants at a median age of 1.7 years (range, 0.3–8.8). Sixty‐three percent of patients with RMA suffered RD, in contrast to 28% of patients with RME. Relapse treatment consisted of conventional CHT ( n = 48), resection ( n = 28), and RT ( n = 21). The pattern of relapse and best resection were significant prognostic factors for patients with RD ( P = 0.000 and P = 0.002). Late effects occurred as secondary malignancies in 6%, long‐term toxicity in 21%, and resection‐related impairment in 33% of the 105 surviving patients. The 5‐year event‐free survival and overall survival for infants with initial LD were 51% and 69%, 14% and 14% for patients with initial MD and 39% and 41% for relapsed patients, respectively. Conclusion: Multimodal treatment including microscopically complete resection is strongly recommended to achieve a good prognosis in LD and RD of infants with RMS.